City economies and microbusiness growth. (November 2017) - Houston, Donald; Reuschke, Darja
In developed countries, microbusinesses (those employing fewer than 10 people) and home-based businesses have been systematically overlooked in urban economic development thinking. This article assesses the influence of city location and being run from the business owner's home on microbusiness growth, based on empirical analysis of panel firm-level data over a four-year period during the UK's long boom. The analysis reveals that cities provide benefits to microbusinesses for turnover growth but not for employment growth – suggesting that the additional growth induced by cities for microbusinesses may be jobless growth. However, in the case of microbusinesses run from the owner's home, cities facilitate growth into medium-sized businesses (with 50+ staff). In conclusion, microbusinesses, including those run from business owners' homes, are integral to the evolution and dynamics of urban economies and essential to understanding the nature of growth in cities. Agglomeration theory needs to say more about how urban agglomeration benefits firms of different types and sizes, and small business and self-employment research needs to say more about the influence of location, in particular cities. How businesses use both commercial and residential property are integral to the nature of growth in cities.